2023
DOI: 10.1002/clt2.12295
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity to change and minimal clinically important difference of the angioedema control test

Lauré M. Fijen,
Carolina Vera,
Thomas Buttgereit
et al.

Abstract: BackgroundThe Angioedema Control Test (AECT) is a patient‐reported outcome measure developed and validated for the assessment of disease control in patients with recurrent angioedema. Its sensitivity to change and minimal clinically important difference (MCID) have hitherto not been established.MethodsPatients with recurrent angioedema due to chronic spontaneous urticaria, hereditary angioedema, or acquired C1‐inhibitor deficiency were repeatedly asked to complete the AECT along with the Angioedema Quality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…reported that the strength of sensitivity to change of AECT‐4wk to detect the change in disease control determined by physicians, angioedema related QoL and patient rated treatment sufficiency was high while it was lower in the detection of change in patients‐self assessment of disease control. However, they did not analyze the correlation between change in AECT‐4wk and change in disease activity and sensitivity to change in AECT‐3mth 11 . We found that changes in AECT‐4wk were sensitive to detect the changes in disease activity, disease control assessed by patients and treatment sufficiency, while less sensitive to detect the changes in AE‐related QoL.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…reported that the strength of sensitivity to change of AECT‐4wk to detect the change in disease control determined by physicians, angioedema related QoL and patient rated treatment sufficiency was high while it was lower in the detection of change in patients‐self assessment of disease control. However, they did not analyze the correlation between change in AECT‐4wk and change in disease activity and sensitivity to change in AECT‐3mth 11 . We found that changes in AECT‐4wk were sensitive to detect the changes in disease activity, disease control assessed by patients and treatment sufficiency, while less sensitive to detect the changes in AE‐related QoL.…”
Section: Discussionmentioning
confidence: 72%
“…Fijen et al. reported that 3‐point change in AECT‐4wk can detect the minimal clinically important improvement in the disease control level of patients with RAE with a sensitivity of 86% and a specificity of 91% 11 . We found that at least 2‐point increase in AECT over 4 weeks could detect a meaningful improvement in disease control with 78.1% sensitivity and 77.6% specificity and at least 3‐3‐point increase with lower sensitivity (68.8%) but better specificity (83.7%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations